Efficacy analysis of 26 cases of ejaculatory duct obstruction treated by prostatic utricle neck endoscopy - Lv, Kun-Long; Sun, Wen-Gong; Zhang, Tian-Biao; Zheng, Tao; Nan, Yong-Hao; Liu, Yong-Fei; Zhou, Yi-Fan; Wang, Rui (Frontiers in Surgery, 2022)
Objective To evaluate the safety and efficacy of transvesical incision in the treatment of ejaculatory duct obstruction. Methods The clinical data of 26 male infertile patients with ejaculatory duct obstruction were retrospectively analysed at the First Affiliated Hospital of Zhengzhou University from June 2020 to August 2021. All patients were treated with seminal vesicle neck incision for ejaculatory duct obstruction. The general clinical characteristics, intraoperative conditions and postoperative effects on the patients were recorded, and the therapeutic effect was evaluated. Results The ejaculatory duct was found through fenestration, and the seminal vesicle gland was smoothly entered in 25 patients (96.2%). Among them, 22 cases underwent bilateral endoscopy and three underwent unilateral endoscopy. Sperm appeared in 23 cases (88.5%) 3 months after surgery. The sperm concentration and motility postoperatively at 6 months were higher than that at 3 months postoperatively. No postoperative complications, such as epididymitis or retrograde ejaculation, occurred. Conclusion Searching for the ejaculatory duct via the neck of the prostatic utricle, assisted by a low-energy holmium laser, is a new method for the treatment of ejaculatory duct obstruction. Microscopic vision is clear using this approach and the postoperative complications are few, which has high value for clinical application.